2020
DOI: 10.48550/arxiv.2009.04267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MoSi2N4 single-layer: a novel two-dimensional material with outstanding mechanical, thermal, electronic, optical, and photocatalytic properties

A. Bafekry,
M. Faraji,
Do M. Hoat
et al.

Abstract: Very recently, the two-dimensional (2D) form of MoSi2N4 has been successfully fabricated [Hong et al., Sci. 369, 670 (2020)]. Motivated by theses recent experimental results, herein we investigate the structural, mechanical, thermal, electronic, optical and photocatalytic properties using hybrid density functional theory (HSE06-DFT). Phonon band dispersion calculations reveal the dynamical stability of MoSi2N4 monolayer structure. Furthermore, the mechanical study confirms the stability of MoSi2N4 monolayer. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…MoN 2 layer is bonded to SiN layers via vertical Si-N bonds with Mo atom located at the center of the trigonal building block of six N atoms. The optimized lattice constants are a=b=2.911 Å, which are in excellent agreement with the previous results [15,17] The tensile strains of monolayer MoSi 2 N 4 are applied in either biaxial or uniaxial (x and y) directions to check its ideal tensile strength. The calculated stress-strain relations of monolayer MoSi 2 N 4 are illustrated in Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…MoN 2 layer is bonded to SiN layers via vertical Si-N bonds with Mo atom located at the center of the trigonal building block of six N atoms. The optimized lattice constants are a=b=2.911 Å, which are in excellent agreement with the previous results [15,17] The tensile strains of monolayer MoSi 2 N 4 are applied in either biaxial or uniaxial (x and y) directions to check its ideal tensile strength. The calculated stress-strain relations of monolayer MoSi 2 N 4 are illustrated in Fig.…”
Section: Resultssupporting
confidence: 86%
“…The moderate band gap, high mobility, and excellent stability of monolayer MoSi 2 N 4 promise its advantages in nano-electronic and optoelectronics. Since the experimental synthesis of layered MoSi 2 N 4 , an enormous amount of research efforts have been devoted to exploring its various properties [17][18][19][20][21][22][23][24][25][26][27]. Density functional theory (DFT) calculations indicated that monolayer MoSi 2 N 4 has a larger Poisson's ratio (0.28) [17] than that of graphene (0.16) [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The valley-dependent properties of monolayer MoSi 2 N 4 , WSi 2 N 4 and MoSi 2 As 4 have been investigated by the first-principle calculations 24 . The structural, mechanical, thermal, electronic, optical and photocatalytic properties of MoSi 2 N 4 are studied by using hybrid density functional theory (HSE06-DFT) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…30 With higher carrier mobility than MoS 2 and better air-stability than phosphorene, MoSi 2 N 4 and its family structure of MA 2 Z 4 monolayers (M represents an early transition metal, A is Si or Ge, Z stands for N, P or As) have soon received much attention. [31][32][33][34][35][36][37][38][39][40][41][42] Nevertheless, there is still lack of band gap engineering study of bilayer MoSi 2 N 4 and WSi 2 N 4 , which is critical for the future application of layered MA 2 Z 4 material in nanoa) Electronic mail: qingyun wu@sutd.edu.sg b) Electronic mail: ricky ang@sutd.edu.sg electronics and optoelectronic devices up to date.…”
mentioning
confidence: 99%